Innovating the Teaching Method by Emphasizing the Leamer's Activities - Vu, Xuân Hùng (Journal of Technical Education Science, 2008)
This paper presents some researches on a number of orientations, viewpoints, and practical bases in the renewal of the teaching method emphasizing the learner's activities. It therefore proposes a number of measures that are likely to enhance the renewal of the didactic methodology centered on the positiveness of the learner's activities in technical- vocational schools.